Kant on Cosmopolitan Education for Peace - Pinheiro Walla, Alice (Con-Textos Kantianos. International Journal of Philosophy, 2018)
Kant sees the gradual implementation of a cosmopolitan world order as necessary for securing peace at national and international level. However, he seems to be overoptimistic about the role of states and other political institutions in securing coordination and peace. In some passages Kant claims that a just juridical framework alone, as long as it is efficiently enforced, is enough to secure a large scale coordination of individual’s agency and a maximal protection of individual freedom. As I will show, other passages suggest that ethical motivation also has an important role to play in the achievement of peace and the implementation of a cosmopolitan world order. This is because good laws alone may produce “good citizens” (who do not infringe the law), but still does not make possible effective political participation and the necessary attitude required for the implementation and improvement of political institutions at national and international level. I will discuss Kant’s claim that education must have a cosmopolitan character as well as the duty of states to create responsible citizens, not only at domestic but also at international level.